The Socially Responsible Organization Lessons from COVID - Mitroff, Ian I. (SpringerBriefs in Organisational Studies,, 2022)
This book explores the nature of the socially responsible organization, specifically the role of crisis management in creating a socially responsible organization. It applies the Myers-Briggs Personality Typology (MBPTI) and the Thomas-Kilmann Conflict Framework to issues such as responses to the COVID-19 pandemic, regulation of tech companies, and infrastructure. Dr. Mitroff lists the major arguments given in regards to these issues and subjects them to the strongest possible scrutiny and critique to hold both individuals and organizations accountable to the larger responsibilities we share as global citizens. This is an open access book.